Multimodal nonlinear optical microscopy with shaped 10 fs pulses - Rehbinder, Jean; Brückner, Lukas; Wipfler, Alexander; Buckup, Tiago; Motzkus, Marcus (Optics express, 2014)
We demonstrate the use of shaped 10 fs pulses for multimodal microscopy. The combination of a broadband oscillator and a pulse shaper provides a flexible light source that can be optimized for various nonlinear effects produced in the sample, either for signal intensity or for selectivity. While the highest nonlinear generation efficiency is achieved with the shortest pulses, more complex waveforms address specific transitions in the sample for better contrast. This is shown experimentally with the imaging of a moss leaf and of human skin biopsies using coherent anti-Stokes Raman scattering, two-photon fluorescence and second harmonic generation signals.